A Newly Identified Frontal Path from Fornix in Septum Pellucidum with 7.0T MRI Track Density Imaging (TDI) – The Septum Pellucidum Tract (SPT) - Cho, Zang-Hee; Chi, Je-Geun; Choi, Sang-Han; Oh, Se-Hong; Park, Sung-Yeon; Paek, Sun Ha; Park, Chan-Woong; Calamante, Fernando; Kim, Young-Bo (Frontiers in Neuroanatomy, 2015)
The high anatomical contrast achieved with the newly emerging MRI tractographic technique of super-resolution track density imaging (TDI) encouraged us to search for a new fiber tract in the septum pellucidum. Although this septum pellucidum tract (SPT) has been observed previously, its connections were unclear due to ambiguity and limited resolution of conventional MRI images. It is now possible to identify detailed parts of SPT with the increased resolution of TDI, which involves diffusion MRI imaging, whole-brain tractography, and voxel subdivision using the track-count information. Four healthy male subjects were included in the study. The experiment was performed with 7.0T MRI, following the guidelines of the institute’s institutional review board. Data were processed with the super-resolution TDI technique to generate a tractographic map with 0.18 mm isotropic resolution. The SPT was identified in all subjects. Based on additional seed tracking method with inter-axis correlation search, we have succeeded in identifying a new frontal lobe pathway in the SPT. We hypothesize that the tract is connected as a superior dorsal branch of the fornix that leads to the prefrontal cortex.